2020
DOI: 10.1111/vsu.13431
|View full text |Cite
|
Sign up to set email alerts
|

Modified cranial closing wedge osteotomy to treat cranial cruciate ligament deficient stifles with excessive tibial plateau angles: Complications, owner satisfaction, and midterm to long‐term outcomes

Abstract: ObjectiveTo report midterm to long‐term outcomes of dogs with cranial cruciate ligament (CCL) rupture and excessive tibial plateau angles (TPA) treated with a modified cranial closing wedge osteotomy (m‐CCWO).Study designRetrospective case series.Study populationDogs (n = 21) with CCL rupture and excessive TPA treated with m‐CCWO (n = 28).MethodsMedical records, midterm and long‐term follow‐up radiographic examination records, Canine Orthopedic Index data, and owner surveys were reviewed to determine functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In our study, precise planning of the osteotomy allowed us to superimpose the AA and MA axes postoperatively, thus reducing the median TLAS to 0°; this resulted in 82.5% of the dogs having strictly aligned axes with consecutive, predictable postoperative TPAs. Furthermore, the reduced angle of correction compared to previous recommendations for standard CCWO [ 4 , 9 , 10 , 12 , 23 ] and the positioning of the tip of the wedge at the caudodistal insertion of the medial collateral ligament rather than at the caudal cortex of the tibia, as described in previous studies [ 6 9 ], reduced the size of the wedge and limited lowering of the patella. As a result of the reduced size and precise positioning of the wedge, the median tibial shortening, even in this cohort of large dogs with large TPAs, was 3.5 mm, comparable to the mean difference in tibial length of 2.5–3 mm for CCWO documented in previous publications [ 6 9 , 16 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In our study, precise planning of the osteotomy allowed us to superimpose the AA and MA axes postoperatively, thus reducing the median TLAS to 0°; this resulted in 82.5% of the dogs having strictly aligned axes with consecutive, predictable postoperative TPAs. Furthermore, the reduced angle of correction compared to previous recommendations for standard CCWO [ 4 , 9 , 10 , 12 , 23 ] and the positioning of the tip of the wedge at the caudodistal insertion of the medial collateral ligament rather than at the caudal cortex of the tibia, as described in previous studies [ 6 9 ], reduced the size of the wedge and limited lowering of the patella. As a result of the reduced size and precise positioning of the wedge, the median tibial shortening, even in this cohort of large dogs with large TPAs, was 3.5 mm, comparable to the mean difference in tibial length of 2.5–3 mm for CCWO documented in previous publications [ 6 9 , 16 ].…”
Section: Discussionmentioning
confidence: 84%
“…PB could be a result of tibial shortening following wedge reduction with standard CCWO and has been reported to be a critical disadvantage of CCWO compared to TPLO [ 11 13 ]. Such shortening could increase the strain on the patellar ligament and increase the likelihood of secondary inflammation, but these are theoretical suggestions that have not been proven or documented in practice [ 6 , 7 , 9 , 10 ]. In our study, precise planning of the osteotomy allowed us to superimpose the AA and MA axes postoperatively, thus reducing the median TLAS to 0°; this resulted in 82.5% of the dogs having strictly aligned axes with consecutive, predictable postoperative TPAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors comment that given the very proximal position of the osteotomy with this technique, they recommend to always supplement plate fixation with cranial pin and figureof-eight tension band wire to protect the tibial tuberosity and prevent loss of reduction at the osteotomy site in the postoperative period (Frederick & Cross 2017). Christ et al (2018) and Terreros & Daye (2020) reported the short-term and long-term outcome after another modification of the CCWO technique aimed at minimising the length of the cranial tibial wedge and optimising bone contact at the osteotomy. We refer the readers to the original papers for a full description of the surgical technique.…”
Section: Surgical Management: Cranial Closing Wedge Ostectomymentioning
confidence: 99%
“…In our study, precise planning of the osteotomy allowed us to superimpose the AA and MA axes postoperatively, thus reducing the median TLAS to 0°; this resulted in 82.5% of the dogs having strictly aligned axes with consecutive, predictable postoperative TPAs. Furthermore, the reduced angle of correction compared to previous recommendations for standard CCWO [4,9,10,12,23] and the positioning of the tip of the wedge at the caudodistal insertion of the medial collateral ligament rather than at the caudal cortex of the tibia, as described in previous studies [6 -9], reduced the size of the wedge and limited lowering of the patella. As a result of the reduced size and precise positioning of the wedge, the median tibial shortening, even in this cohort of large dogs with large TPAs, was 3.5 mm, comparable to the mean difference in tibial length of 2.5-3 mm for CCWO documented in previous publications [6 -9, 16].…”
Section: Discussionmentioning
confidence: 85%